The Influence Principal's Leadership, Work Climate, and Work Motivation on the Performance of High School Education Personnel in Malinau Regency - Yulianti Bela; Cepi Safruddin Abdul Jabar (EDUCATION JOURNAL OF INDONESIA, 2026)
Research on the influence of the principal's leadership, work climate, and work motivation on the performance of high school education personnel in Malinau Regency aims to find out: 1) The influence of the principal's leadership on the performance of education personnel in Malinau. 2) The effect of the work climate on the performance of education personnel in Malinau. 3) The effect of work motivation on education personnel in Malinau. 4) The influence of the principal's leadership, work climate and work motivation together on the performance of education personnel in Malinau. This research uses correlational through a quantitative approach. The population in this study is all high school education personnel in Malinau Regency, consisting of civil servants and non-civil servants. The sample in this study amounted to 34 people taken using total sampling. The instrument used is using a closed questionnaire. The data analysis techniques used are independent ttests and simple linear regression. The research results show that: (1) There was an influence of the principal's leadership on the performance of high school education personnel with a contribution of 75.4%. (2) There was an influence of the work climate on the performance of high school education personnel with a contribution of 84%. (3) There was an influence of work motivation on the performance of high school education personnel with a contribution of 81.2%. (4) There was an influence of the principal's leadership, work climate and work motivation together on the performance of high school education personnel with a contribution of 85.7%.